Avaliação de defeitos resistivos de manufatura em SRAMs frente ao fenômeno de NBTI - Martins, Marco Túlio Gonçalves (2016)
With advances in technology and miniaturization of CMOS, reliability during the life cycle of Integrated Circuit (IC) becomes a complex concern for critical applications. Miniaturization brings many benefits as high performance, power consumption and increase number of functions inside of IC. However, alongside with these, the benefits for increase of interconnections and density of such SoCs create new challenges for the industry. Moreover, a chip needs to store more and more information, resulting in the fact that SRAM occupy the greatest part of SoCs. Consequently, technology advances need to increase the transistor‘s density, turnning them a critical concern for testing and reliability to be analysed after manufacturing, since it creates new types of defects. Defects during manufacture process, as well as Negative Bias Temperature Instability (NBTI), Hot Carrier Injection (HCI) and Electromagnetic Interference (EMI) phenomena represent important challenges that must be addressed at an early stages and over the IC‘s life-time. In this context, understanding these phenomena and how they affect technologies below 65nm is essential to ensure reliability required for critical applications. In addition, another source of defects is related to process variations during manufacture. Such defects, like resistive-open and resistive-bridge, appear as the most incident. These defects occur due to small geometric changes in the cell, resulting in static and dynamic failures. Depending on the size of defect they can be considered as weak-defects, which do not result in faulty behaviour at logic level and are not sensitized in conventional manufacturing tests. Note that dynamic faults are considered most responsible for testescapes during manufacturing test. Another important phenomena that affects the reliability of ICs over time is NBTI, causing the aging of SRAMs. In this context, this work proposes to analyze the impact of NBTI in SRAM cells with weak resistive-open and resistive-bridge defects that can escape manufacturing tests due to their dynamic behaviour but, with aging, may become dynamic faults over time.